Evaluation of Controller Strategies in Air Traffic Management for KLFIR Oceanic Sector / Mohamad Fuad Sidik ...[et al.] - Sidik, Mohamad Fuad; Abdul Rahman, Siti Mariam; Wan Mohamed, Wan Mazlina (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Air Traffic Control (ATC) is a service provided by ground to control movement of all aircraft within a controlled airspace. This is done by using either Radar Control or Procedural Control depending on the availability of radar system in the area. In Peninsular Malaysia, these controlled areas are known as Kuala Lumpur Flight Information Region (KLFIR). These areas are divided into 6 Sectors that was assigned to a different team of controllers. As this research is aimed at examining the strategies used by Air Traffic Controller (ATCO) during Procedural Control, Lumpur Oceanic Sector or Lumpur Sector 4 was chosen as the participating controlled airspace. To gather insights on controller strategies, participants from Kuala Lumpur Air Traffic Control Centre (KLATCC) have volunteered to participate in Static Conflict Detection Exercise (SCDE). Based on the results, the most prominent issue that can be highlighted was on delays, where it is seen as unavoidable in regulating air traffic. However, it is also gathered that some minimum differences between Requested Cruising Altitude (FPL) and Assigned Cruising Altitude (XFL) can be achieved by pre-planning the traffic prior to Estimated Time of Departure (ETD). Also, by doing so, the controller workload may be reduced by 45% in average, as reported by the participants. As there are several control strategies that can be used, regards to the airlines operation cost is important in selecting the best strategy that may benefit both controller and airlines. Additionally managing traffic would be more manageable as available cruising altitude will be known at any given time as a result from the pre-planning exercise.